BIMBINGAN AKHLAK REMAJA DAN PENINGKATAN MORAL DI DESA JAYASAMPURNA - Fadhilah, Muhammad Rijal; Mulyadi, Acep; Irham, Irham (Universitas Islam 45 Bekasi, 2024)
Guidance on teenage morality is an educational program designed to strengthen moral values and ethics in the daily lives of teenagers. The program aims to help teenagers develop awareness of moral norms and reinforce positive character and behavior. Implemented in Desa Jayasampura, this program involves active interaction between facilitators and teenagers, focusing on the moral situations and challenges faced by teenagers in their local environment. Through a participatory approach and group activities, teenagers are encouraged to understand the concepts of morality in Islam and how to apply them in their daily lives. Moral guidance includes discussions on integrity, responsibility, empathy, and respect for oneself and others. Practical activities such as discussions, role-playing games, and community-based projects are used to engage teenagers in the learning process. Evaluation of this program will be conducted by measuring changes in attitudes, knowledge, and behavior of teenagers before and after participating in moral guidance. The results of this evaluation are expected to provide a better understanding of the program's effectiveness in increasing moral awareness and strengthening ethical values among teenagers at the local level. Thus, it is hoped that this program will make a positive contribution to shaping the character and morality of teenagers in Desa Jayasampurna.